Libarian Competence Development in Supporting Scientific Publication Guidance Services at Library of Sebelas Maret University - Dian Hapsari; Adriana Grahani Firdausy; Haryanto Haryanto (Edumaspul: Jurnal Pendidikan, 2023)
The aim of this research is to analyze the development of librarian competencies related to scientific publication guidance services. This research uses qualitative methods with a descriptive approach, data analysis using Miles and Huberman. Respondents totaled 30 people, consisting of lecturers, students, and librarians. The data collection instruments used in this research were observation, interviews and documentation. The results of research on the concept of librarian competency development related to scientific publications. The research outcome is to find a model for developing librarian competency in supporting scientific publication guidance services at the Sebelas Maret University Library.